Pathways of [Ca2+]i rise evoked by angiotensin II in MDCK renal tubular cells. (December 2013) - Liu, Chung-Pin; Chou, Chiang-Ting; Liang, Wei-Zhe; Cheng, Jin-Shiung; Chang, Hong-Tai; Kuo, Daih-Huang; Ko, Kuang-Chung; Chiang, Ni-Na; Wu, Ru-Fang; Shieh, Pochuen; Jan, Chung-Ren
Abstract The effect of angiotensin II (Ang II) on cytosolic Ca2+ concentrations ([Ca2+]i) in MDCK renal tubular cells was explored. The Ca2+-sensitive fluorescent dye fura-2 was applied to measure [Ca2+]i. Ang II at concentrations of 5–40 µM induced a [Ca2+]i rise in a concentration-dependent manner. The response was reduced partly by removing Ca2+. Ang II evoked store-operated Ca2+ entry that was inhibited by La3+ and Gd3+. In the absence of extracellular Ca2+, incubation with the endoplasmic reticulum Ca2+ pump inhibitor 2, 5-di-tert-butylhydroquinone (BHQ) or thapsigargin abolished Ang II-induced Ca2+ release. Inhibition of phospholipase C with U73122 abolished Ang II-induced [Ca2+]i rise. Three Ang II analogues [(ASN1, VAL5)-Ang II acetate, (SAR1, THR8)-Ang II acetate, (VAL5)-Ang II acetate] failed to induce a [Ca2+]i rise. Together, in MDCK cells, Ang II induced a [Ca2+]i rise via Ca2+ entry through store-operated Ca2+ channels and phospholipase C-dependent Ca2+ release from the endoplasmic reticulum. Moreover, Ang II's amino acid sequence is important in its stimulatory effect on [Ca2+]i.